Invertibility of 2 × 2 operator matrices. Issue 11 (26th August 2019) - Huang, Junjie; Sun, Junfeng; Chen, Alatancang; Trunk, Carsten
Abstract: Properties of right invertible row operators, i.e., of 1 × 2 surjective operator matrices are studied. This investigation is based on a specific space decomposition. Using this decomposition, we characterize the invertibility of a 2 × 2 operator matrix. As an application, the invertibility of Hamiltonian operator matrices is investigated.